Pengaruh Penggunaan Uap Kering Pada Proses Pirolisis Limbah Plastik - R.Y.P, Lalu Junaedi; Sudia, Budiman; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2019)
Pyrolysis is a fascination process by increasing temperatures without or less oxygen. This research aims to compare the use of gas pressure and gas-burning temperatures that were hasyfish. In this study, the reabsorption of 500 gr in the druse variable of the interactive waste is the type of PET (Polyethylene) with two types of the pyrolysation of the pyrolysis without being dry and the pyrolysis is with the athletes. Research began in preparation for the preparation of the test, preparation of ryl, precursors and research with gas pyrolysis. Further conducted analysis for each product. The highest gas pressure has a pyrolysation trial with an average of 0,04125 MPa while for the pyrolysis, without either a 0,02375 MPa while the average gas of the highest gas air date on the test pyrolysis without a dry temperature at 971,5 °C whereas the water is called for the water of the process of the 962,75 °C.Keywords: Pyrolysis, plastic garbage, gas, and dry steam